2019
DOI: 10.1002/chem.201904751
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Decarboxylative Amino‐Fluoroalkylation of Maleic Anhydride

Abstract: A photoinduced decarboxylative three‐component coupling reaction involving amine, maleic anhydride, and fluorinated alkyl iodides has been developed, leading to synthetically valuable fluoroalkyl‐containing acrylamides with a high E selectivity. A broad array of substrates including monoprotected amino acid are capable coupling partners. Preliminary mechanistic studies suggest a stepwise process. This reaction represents the first example of photoinduced decarboxylative difunctionalization of maleic anhydride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Fluoroalkylated E ‐configured acrylamides can also be accessed from maleic anhydride and amines via tandem ring opening decarboxylative fluoroalkylation (Scheme 57). [186] The reaction proceeds under photoredox conditions employing Ru(bpy) 3 Cl 2 as a catalyst for the formation of fluoroalkyl radical (oxidative quenching with IR F ) and oxidative decarboxylation.…”
Section: Multicomponent Reactionsmentioning
confidence: 99%
“…Fluoroalkylated E ‐configured acrylamides can also be accessed from maleic anhydride and amines via tandem ring opening decarboxylative fluoroalkylation (Scheme 57). [186] The reaction proceeds under photoredox conditions employing Ru(bpy) 3 Cl 2 as a catalyst for the formation of fluoroalkyl radical (oxidative quenching with IR F ) and oxidative decarboxylation.…”
Section: Multicomponent Reactionsmentioning
confidence: 99%
“…The photoinduced decarboxylative difunctionalization of maleic anhydride with amine and fluorinated alkyl iodides was reported by the Zhang group (Scheme 58). 131 A variety of fluorinated alkyl halides and amines reacted smoothly in this reaction. The difluoroalkyl radical which was generated from oxidative quenching reaction between fluorinated alkyl iodides and excited Ru(II)* was also possible in this reaction.…”
Section: Scheme 53mentioning
confidence: 99%
“…Again a single example with maleic anhydride was reported and a similar ring opened product was observed; however, decarboxylation did not occur in this case such that the maleic acid adduct was formed (Scheme c). In 2020, Zhang reported a decarboxylative amino-alkylation of maleic anhydrides by using anilines as the nucleophile to open maleic anhydride . Zhang observed that the second decarboxylation occurs via a radical process that reinstalls the olefin for the synthesis of acrylamides; similar olefin formation is not observed in our reaction.…”
mentioning
confidence: 93%